2000
DOI: 10.1007/s12043-000-0055-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic sheath at the boundary of a collisional dusty plasma

Abstract: Considering the Boltzmann response of the ions and electrons in plasma dynamics and inertial dynamics of the dust charged grains in a highly collisional dusty plasma, the nature of the electrostatic potential near a boundary is investigated. Based on the fluid approximation, the formation as well as the characteristic behaviours of the sheath is studied. It is expected that the presence of dust charged grains will lead to a very different behaviour of the sheath as compared to that of electron-ion plasma. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This is followed by the interest to extend the study in magnetized plasma contaminated by dust charge grains (Baishya and Das 2003;Das and Kalita 2004). Because of dust charged grains in plasma, a new mode called dust acoustic mode (DAW) (Rao et al 1990) can be found in nonlinear plasma-acoustic wave dynamics which has been confirmed latter by the experimental studies of Barkan et al (1995). Recently Tian (2006a, 2006b), Tian and Gao (2005) have yielded the effectiveness of dust grains in the formation of stable dust atmosphere in various region in space.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This is followed by the interest to extend the study in magnetized plasma contaminated by dust charge grains (Baishya and Das 2003;Das and Kalita 2004). Because of dust charged grains in plasma, a new mode called dust acoustic mode (DAW) (Rao et al 1990) can be found in nonlinear plasma-acoustic wave dynamics which has been confirmed latter by the experimental studies of Barkan et al (1995). Recently Tian (2006a, 2006b), Tian and Gao (2005) have yielded the effectiveness of dust grains in the formation of stable dust atmosphere in various region in space.…”
mentioning
confidence: 98%
“…In continuation Das et al (1999) derived the plasma sheath in plasma to show salient features of electron absorbing wall and described the effect of finite ion temperature as for the required condition in forming sheath in plasmas. Further, theoretical developments on studying sheath have been done by the incorporation of different effects like the presence of magnetic field (Baishya and Das 2003), ionization (Das and Devi 2006) and collision effect (Baishya et al 2000). While Liu et al (2003), Lei et al (2006), Alterkop (2004) and other workers have shown the experimental evidences on the formation of plasma sheath so as to alleviate the uneven competition between theory and experiments.…”
mentioning
confidence: 99%